Analisis Faktor Resiko Ketuban Pecah Dini Di Rsud Mukomuko Kabupaten Mukomuko Tahun 2021 - Sulastri Sulastri; Meri Epriana Epriana (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2021)
Premature rupture of membranes is very dangerous for pregnant women and their babies, the danger of premature rupture of membranes is infection occurs in mother and baby. The rupture of the membranes leaves the baby unprotected by the amniotic membrane and exposed to contact with the outside world, which causes bacteria to enter the mother's womb and infect both mother and baby. This can be life-threatening for both mother and baby. In addition, the birth of a baby that is less than the normal time causes premature babies and the risk of fetal defects is high. The purpose of this study was to analyze the risk factors for premature rupture of membranes in Mukomuko Hospital, Mukomuko Regency. The method used is descriptive-analytical research design using a case-control design. The population in this study were all mothers who gave birth at the Mukomuko Hospital, the sample in this study amounted to 100 people with a ratio of case and control groups of 1:1. Case samples (cases) were taken by total sampling, namely (50 mothers who gave birth with PROM), while the control sample was taken by random sampling from the entire population who did not experience premature rupture of membranes. Bivariate statistical test using Chi-square (X²). The results of univariate analysis most of the respondents (74.0%) were not infected, most of the respondents (71.0%) did not do pregnancy exercise, most of the respondents (54.0%) were primiparous, most of the respondents (82.0%) had no history of premature rupture of membranes, some respondents (50.0%) experienced premature rupture of membranes and some respondents (50.0%) did not experience premature rupture of membranes. The results of the bivariate analysis showed that there was a relationship between infection, pregnancy exercise, parity, and a history of PROM with the incidence of premature rupture of membranes. It is hoped that the hospital must have socialization of pregnancy exercise and the dangers of KPD in pregnant women.